MITIGASI DAN PENANGGULANGAN BENCANA BANJIR DEBRIS PASCA GEMPA PALU 2018 - Cosmas Bambang Sukatja; Banata W.R; Perdi Bahri (Pusat Litbang Sumber Daya Air, Kementerian Pekerjaan Umum dan Perumahan Rakyat, 2021)
The 7.4 SR earthquake which occurred in The Donggala Regency, Central Sulawesi on September 28th 2018 was a shallow earthquake due to the Palukoro fault activity. The impact of the quake’s shaking created pressure on the rock and soil masses of 77 hilly locations in the Palu, Sigi, and Donggala, causing several landslides and the increasing the potential of more. One of the slopes of at risk of landslides which can trigger debris flow is found on the hills of Poi Village, Dolo Selatan District, Sigi Regency. The estimated volume of lose material which could fall in a landslide is 4.8 million m3. Rainfall in the area is predicted to trigger debris flow with the potential to bury settlements and block the flow of the Palu tributary located downstream. For this reason, it is necessary to conduct a study of the lose material deposits in the Poi River channel which can trigger debris flows during the rainy season. The problem-solving method in this study used is a rationalistic and descriptive qualitative approach. In predicting the distribution direction, propagation and hydrograph of the debris flow ths study applies the numerical modelling SIMLAR 2.1. This debris disaster risk management effort uses Sabo technology physically and non-physically. Keywords: earthquakes, landslides, debris flow, debris disaster management, Sabo technology physically and non-physically.